Letter - Winstanley, E.
029-0116-001 Telegraphic Address: "WHOLESALE MANCHESTER" Telephone: BLACKFRIARS 1212. Extension No. Please Address Your Reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C 6th and 7th editions; Western UNION 5 Letter; BENTLEY COMPLETE PHRASE; Bentley second phrase; A.1. Marconi, and private. Our reference 9513/ST/JEM Your reference 16th July, 1937. The Trades Union Congress General Council, Transport House, Smith Square, LONDON. S.W.1. Dear Sirs, We have available a special line of 200 cases of Sweetened Condensed Milk which we are prepared to clear at the special price of 20/- per case, each containing 48 - 1's. We have in mind the fact that you are buying various lines of foodstuffs from time to time for shipment to Spain for relief purposes and we are wondering whether this offer will be of any interest to you from this point of view. The quotation of 20/- per case is based f.o.b. English port and includes all packing charges. If you are interested we shall be glad to have your instructions in due course, and meanwhile remain, Yours faithfully, E. Winstanley Export Department. 292/946/29/116